Clozapine-Induced Myocarditis: A Case Report of an Adolescent Boy with Intellectual Disability - Lila Aboueid; Nitin Toteja (Case Reports in Psychiatry)
Background. Although known for its efficacy in treatment-resistant schizophrenia, the usage of clozapine has been limited due to concerns over potential adverse effects. Myocarditis, one potential fatal complication, can develop at any point during treatment but has been most commonly observed 2-3 weeks after clozapine initiation. Objective. A case of acute clozapine-induced myocarditis is described, highlighting the history, onset, and treatment course of presentation. There is a need to raise awareness of this potential complication, especially in the pediatric population. Results. 17-year-old Puerto Rican boy, with history of schizophrenia, disorganized type (treatment resistant), and intellectual disability, developed myocarditis on the thirteenth day following clozapine commencement. Initial presenting symptoms included tachycardia, lethargy, and vague gastrointestinal distress. Patient fully recovered after supportive medical care and clozapine discontinuation. Conclusions. Myocarditis is a known potential complication of clozapine initiation; however, due to its limited usage in the pediatric population, reported cases are limited. There is a need to establish evidence-based monitoring guidelines for clozapine usage, particularly in the pediatric population where the presentation may be atypical and clinical suspicion may be overlooked.